Human Cerebrospinal Fluid Induces Neuronal Excitability Changes in Resected Human Neocortical and Hippocampal Brain Slices - Wickham, Jenny; Corna, Andrea; Schwarz, Niklas; Uysal, Betül; Layer, Nikolas; Honegger, Jürgen B.; Wuttke, Thomas V.; Koch, Henner; Zeck, Günther (Frontiers in Neuroscience, 2020)
Human cerebrospinal fluid (hCSF) has proven advantageous over conventional medium when culturing both rodent and human brain tissue. Increased excitability and synchronicity, similar to the active state exclusively recorded in vivo, reported in rodent slice and cell-cultures with hCSF as recording medium, indicates properties of the hCSF not matched by the artificial cerebrospinal fluid (aCSF) commonly used for electrophysiological recording. To evaluate the possible importance of using hCSF as electrophysiological recording medium of human brain tissue, we compared the general excitability in ex vivo human brain tissue slice cultures during perfusion with hCSF and aCSF. For measuring the general activity from a majority of neurons within neocortical and hippocampal human ex vivo slices we used a microelectrode array (MEA) recording technique with 252 electrodes covering an area of 3.2 x 3.2 mm2. A second CMOS-based MEA with 4225 electrodes on a 2 x 2 mm2 area was used for detailed mapping of action potential waveforms. We found that hCSF increases the number of active neurons and the firing rate of the neurons in the slices as well as increases the numbers of bursts while leaving the duration of the bursts unchanged. Interestingly, not only an increase in the overall activity in the slices was observed, but a reconfiguration of the network could be detected with specific activation and inactivation of subpopulations of neuronal ensembles. In conclusion, hCSF is an important component to consider for future human tissue studies, especially for experiments designed to mimic the in vivo situation.